A thin hybrid circuit-analog (CA) microwave absorbing double-slab composite structure. (June 2015) - Choi, Won-Ho; Shin, Jae-Hwan; Song, Tae-Hoon; Kim, Jin-Bong; Lee, Woo-Yong; Kim, Chun-Gon
Abstract: In this study, a thin hybrid circuit-analog (CA) microwave absorbing double slab composite structure is presented. Unlike conventional CA absorbers, the composite spacer in the proposed structure is made up of a glass/epoxy and high permittivity layer of glass/epoxy-MWCNT composite, which contributes to the stable absorption performance in the curved surface while maintaining the thin thickness of the composite spacer. To design the microwave absorber, the genetic algorithm which is the most used evolutionary algorithm technique in this field was used. The total thickness of the designed double slab CA absorber was very thin thickness of 2.37 mm. Although the designed absorber has very thin thickness, it could satisfy the −10 dB absorption in whole X-band (8.2–12.4 GHz). The absorbing performance of the designed absorber was compared with other types of absorber. Also, to check the absorbing performance of the proposed structure in the curved surface, the echo radar cross section (RCS) was simulated in the X-band with other types of absorber. The simulated results proved an excellent performance of a proposed novel double slab CA absorber.